1996
DOI: 10.1161/01.str.27.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin Resistance Associated With Compensatory Hyperinsulinemia in Ischemic Stroke

Abstract: Insulin resistance in association with compensatory hyperinsulinemia and dyslipidemia may be an important pathogenetic factor underlying the development of atherothrombotic infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…The high proportion of largeartery occlusive infarctions among ischaemic strokes (approximately 60-70%) [17], and the positive association between diabetes and the risk of ischaemic stroke among Western populations, suggest that diabetes also increases the risk of large-artery occlusive infarction. The results of a retrospective, case-controlled study indicate that this is also the case in the Japanese population [18].…”
Section: Discussionmentioning
confidence: 74%
“…The high proportion of largeartery occlusive infarctions among ischaemic strokes (approximately 60-70%) [17], and the positive association between diabetes and the risk of ischaemic stroke among Western populations, suggest that diabetes also increases the risk of large-artery occlusive infarction. The results of a retrospective, case-controlled study indicate that this is also the case in the Japanese population [18].…”
Section: Discussionmentioning
confidence: 74%
“…The following potential reasons for this were considered: the mean age of the subjects included in the analysis was 56, which is otherwise associated with a relatively low prevalence of cerebrovascular disorder; patients who were under treatment for hypertension and diabetes were excluded from the study, resulting in a sample with only a low risk of cerebrovascular disorder; and mild transient ischemic attack might have been missed in the present study. Moreover, in a previous study of Japanese subjects, it was found that the percentage of subjects with insulin resistance was significantly high but only in the atherothrombotic infarction group, and not in groups with other types of cerebrovascular disorder (20).…”
Section: Discussionmentioning
confidence: 86%
“…The adverse effects of IR on the peripheral and coronary circulations have been studied extensively, and vascular dysfunction emerges as a major factor in the development of hypertension and coronary artery disease (5)(6)(7)(8)(9)(10). In sharp contrast, changes in regulatory mechanisms of the cerebral circulation are virtually unexplored, despite the fact that IR, as well as type 2 diabetes, increases the prevalence of cerebrovascular events, and IR patients with stroke are subject to more severe progression, slower recovery, and higher mortality (11)(12)(13)(14). In addition, obesity and IR in older people are risk factors for dementia, particularly Alzheimer's disease (15)(16)(17), which might be related to cerebrovascular dysfunction and chronic hypoperfusion of the brain (18,19).…”
mentioning
confidence: 99%